The Influence of Product Quality, Product Design, and Promotion on Furniture Purchase Decisions for Pets in Jakarta - Natashya Natashya; Elfrida Viesta Napitupulu (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the influence of product quality, product design, and promotion on consumer purchasing decisions for pet furniture in Jakarta. The background of this research is driven by the increasing trend of pet humanization, where pets are no longer considered mere companions but are treated as family members, leading to higher demand for premium and aesthetically pleasing products. The research employs a quantitative causal design with data collected through online and offline questionnaires distributed to pet owners who have purchased furniture or accessories for their pets. Purposive sampling was used to ensure the selection of respondents with relevant experience, resulting in 220 valid responses. Data were analyzed using multiple linear regression with SPSS Statistics 27. The findings reveal that product quality, product design, and promotion each have a positive and significant influence on purchasing decisions. Product quality emerged as the most dominant factor, followed by product design and promotion. These results highlight the importance of providing durable, safe, and premium-quality furniture while integrating innovative design that aligns with modern interior trends and effective promotional strategies, particularly through digital platforms. The implications of this study suggest that businesses in the pet furniture industry should focus on improving product standards, developing designs that combine functionality with aesthetics, and optimizing promotional efforts to meet consumer expectations and enhance competitiveness in the growing Indonesian pet market.